Construction and validation of a transmembrane 4 superfamily-related genes prognostic model for esophageal squamous cell carcinoma - Hao, Xin; Ding, Hao; Zhu, Hongyu; Gong, Xiaoying; Chang, Yuxin; Liu, Chunhua; Hou, Sicong (Frontiers in Oncology, 2025)
BackgroundEsophageal squamous cell carcinoma (ESCC), a virulent form of cancer, markedly diminishes prospects for patient survival. The transmembrane 4 superfamily (TM4SF)-related genes (TRGs) are instrumental in the advancement and spread of cancer. The intent of the current research was to create a prognostic model for ESCC, grounded in the expression patterns of TRGs;MethodsThe datasets pertaining to ESCC from The Cancer Genome Atlas (TCGA)-ESCC and the GSE53622 cohort were meticulously examined. Differential and regression analyses discerned the pivotal signature genes. Subsequent stratification of patients into distinct risk groups was achieved by employing optimal risk score thresholds. This prognostic precision of model was assessed with Kaplan-Meier (K-M) curves and receiver operating characteristic (ROC) analyses. A nomogram integrating risk score with clinicopathological characteristics was meticulously constructed and subsequently validated. Additional analyses included functional enrichment, immune infiltration, immunotherapy responses, drug sensitivity, and molecular network analysis. The expression levels of the characteristic genes were meticulously examined in both TCGA-ESCC datasets and patient-derived tissues;Results24 candidate genes were identified. Among these, TSPAN15, TSPAN9, and TSPAN16 were selected as signature genes. The model showed high prediction accuracy via K-M and ROC curves. Prognostic evaluations have indicated that the risk score and the stage of the tumor are pivotal prognostic indicators. The high-risk cohort exhibited elevated dysfunction scores, suggesting a potentially more favorable response to immunotherapy. Significant drug sensitivity differences were observed. GATA2 regulated all three signature genes, with TSPAN15 and TSPAN16 downregulated and TSPAN9 upregulated. These findings were consistent with RT-qPCR and immunohistochemical results;ConclusionsTSPAN15, TSPAN9, and TSPAN16 are TM4SF-related signature genes with prognostic value for ESCC, providing a theoretical foundation for its diagnosis and treatment.